Revealing the lethal effects of Pasteurella multocida toxin on multiple organ systems - Yuan, Jianlin; Li, Jinfeng; Du, Senyan; Wen, Yiping; Wang, Yiping; Lang, Yi-Fei; Wu, Rui; Yan, Qi-Gui; Zhao, Shan; Huang, Xiaobo; Zhao, Qin; Cao, San-Jie (Frontiers in Microbiology, 2024)
Pasteurella multocida toxin (PMT) is one of the most important virulence factors of Pasteurella multocida type D. Pasteurella multocida infection has caused enormous economic losses in the pig farming industry. Although it is well known that this bacterial infection causes progressive atrophic rhinitis, its effects on other organ tissues in pigs are unclear. In this study, PMT was expressed and purified, and the cytotoxic effects of PMT on four types of swine cells, LLC-PK1, PAM, IPEC, and ST, were investigated. LLC-PK1 exhibited the highest sensitivity to the cytotoxic effects of PMT. Our studies revealed that a PMT concentration of 0.1 μg/kg can lead to weight loss, whereas a PMT concentration of 0.5 μg/kg can lead to death in mice. PMT causes damage to the intestines, kidneys, lungs, livers, and spleens of mice. Furthermore, PMT caused acute death in pigs at treatment concentrations greater than 5 μg/kg; at PMT concentration of 2.5 μg/kg, weight loss occurred until death. PMT mainly caused damage to the hearts, lungs, livers, spleens and kidneys of pigs. The organ coefficient showed that damage to the heart and kidneys was the most severe and caused the renal pelvis and renal pyramid to dissolve and become cavitated. Pathology revealed hemorrhage in the lungs, liver, and spleen, and the kidneys were swollen and vacuolated, which was consistent with the damaged target organs in the mice. In conclusion, these findings demonstrate that PMT is extremely toxic in vitro and in vivo, causing damage to various organs of the body, especially the kidneys and lungs. This study provides a theoretical basis for the in-depth exploration of the cytotoxic effects of PMT on target organs.